(untitled) (Bangladesh Journal of Plastic Surgery, 2014)
Background:. The primary breast augmentation surgery was not popular for a long time in Bangladesh but with the gradual economic and educational development, as well as availability of silicone gel implant and skilled surgeons, the demand, popularity and acceptance of this surgery is increasing. Objective:This study was done to assess the efficacy of the implants in 30 consecutive patients who presented for breast augmentation . Methods:Data were prospectively collected for all patients who underwent bilateral breast augmentation between July 2011 to November 2012 . Breast augmentation was performed by placing textured, round, silicone gel implant in subglandular position via inframammary approach. The 30 patients included in this series were analyzed according to demographic details, preoperative findings, postoperative patient and observer satisfaction scores, and complications. Standard pictures were taken before surgery and during follow-up visits over 6 month; standardised objective measurements of breast and chest were also taken. The test statistics used to analyze the data were descriptive statistics and repeated measure ANOVA .A Visual Analogue Scale (VAS) was used to evaluate the subjects global impression of clinical improvement and one independent observer visually reviewed pre and postoperative result to grade aesthetic results Results: Observers evaluation by predefined criteria (volume, shape, consistency, inframammry fold and scar) rated 60 % of patients with excellent outcome, 30% good, 10% fair and none had poor score .A significant percentage (63.3%) of the 30 patients rated their satisfaction as very good and nine (30%) patient rated as good. None of the patients responded the result as poor or as very poor. No serious complications such as implant malposition or significant capsular contracture were observed Conclusions: We conclude that round textured cohesive gel implants provide excellent results, are well accepted by patients and most short-term postoperative adverse effects following cosmetic implantation are clinically insignificant and do not require treatment. DOI: http://dx.doi.org/10.3329/bdjps.v4i1.18689 Bangladesh Journal of Plastic Surgery January 2013, 4(1): 20-28